2013
DOI: 10.3168/jds.2012-5921
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Comparison of pH, volatile fatty acids, and microbiome of rumen samples from preweaned calves obtained via cannula or stomach tube

Abstract: The objective of this study was to compare rumen samples from young dairy calves obtained via a stomach tube (ST) or a ruminal cannula (RC). Five male Holstein calves (46±4.0 kg of body weight and 11±4.9 d of age) were ruminally cannulated at 15 d of age. Calves received 4 L/d of a commercial milk replacer (25% crude protein and 19.2% fat) at 12.5% dry matter, and were provided concentrate and chopped oats hay ad libitum throughout the study (56 d). In total, 29 paired rumen samples were obtained weekly throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 14 publications
(14 reference statements)
9
26
0
Order By: Relevance
“…Overall, we found that there was no impact of different sampling techniques and sampling sites on the composition of the rumen microbiome in the collected samples based on next-generation sequencing. This observation is similar to previous studies on rumen microbiomes in calves, sheep, goats, and beef cattle using the traditional PCR-DGGE method [3][4][5] and a recent study on rumen microbiomes in Holstein and Jersey cattle using next-generation sequencing [6]. Therefore, the stomach tube can be a feasible alternative method to collect representative samples of the rumen digesta from Hanwoo steers, which will contribute to investigating the composition of the rumen microbiome by increasing the number of animals that can be sampled.…”
Section: Figsupporting
confidence: 91%
See 2 more Smart Citations
“…Overall, we found that there was no impact of different sampling techniques and sampling sites on the composition of the rumen microbiome in the collected samples based on next-generation sequencing. This observation is similar to previous studies on rumen microbiomes in calves, sheep, goats, and beef cattle using the traditional PCR-DGGE method [3][4][5] and a recent study on rumen microbiomes in Holstein and Jersey cattle using next-generation sequencing [6]. Therefore, the stomach tube can be a feasible alternative method to collect representative samples of the rumen digesta from Hanwoo steers, which will contribute to investigating the composition of the rumen microbiome by increasing the number of animals that can be sampled.…”
Section: Figsupporting
confidence: 91%
“…Several studies have shown that the stomach tube is a feasible alternative to rumen cannulation in sheep, goats, calves, and cattle based on comparison of the composition of rumen microbiomes using the traditional polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) method [3][4][5]. In addition, Paz et al [6] showed that the rumen microbiome was similar between stomach…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to surgically-modified animals is not universal, and therefore less invasive techniques, such as oral stomach probing, have been used as an alternative. In the relatively few studies that have compared sampling through the rumen cannula or by stomach probing, differences in fermentation profile and microbiota have been reported in some (e.g., Geishauser and Gitzel, 1996;Duffield et al, 2004) but not all cases (e.g., Lodge-Ivey et al, 2009;Shen et al, 2012;Terré et al, 2013). Part of the discrepancy between studies may reflect differences in the procedures used to avoid salivary dilution and contamination, the type of samples collected and rumen sampling site.…”
Section: Sampling Proceduresmentioning
confidence: 77%
“…These symbionts are capable of fermenting host-indigestible feed into nutrient sources usable by the host, such as volatile fatty acids (1,2). Ruminants are born without a functional rumen and are thought to acquire their digestive microbes from the environment as the rumen develops (3)(4)(5)(6). Although the means by which ruminants acquire this ruminal microbial community remains unclear, the membership and stability of the ruminal community can have a direct and measurable impact on host function and health (7).…”
mentioning
confidence: 99%